(untitled) (Research, Society and Development, 2024)
The morphometry and terrain analysis in a watershed are decisive factor in the study of geomorphological pattern and process. Nowadays, the use of Remote Sensing and hydrological modeling provide a huge amount of data and automatic functions extracted from Digital Elevation Models (DEMs) incorporated into a Geographic Information System (GIS), making it possible to investigate hydrological process and environmental characteristics of the landscape. Morphometric analysis is quantitative evaluation that are essential for understanding the morphological attributes of the drainage network in relation to the landform and flow pattern of the watershed. They also help to access morphogenetic process with implication for ecological policies. With this in mind, the main goal of this research was to use morphometric and geomorphological variables to investigate and characterize of the Gramame watershed located on the south coast of the Paraíba state, Northeastern Brazil. These data has proved essential for understanding of geomorphological and hydrological processes within the basin, and also contribute to the stimulating research within a watershed. Topographical sheets are basic tools in the investigation of watershed. Using information obtained from these maps and the values derived from Digital Elevation Model, morphometric variables were generated that include dimensional and dimensionless measurements as well as geomorphic properties of the drainage basin. The results indicate a strong tectonic control on the drainage network. The value obtained suggests that the study area is not prone to flooding and large-scale mass movements under normal rainfall regime.